2016
DOI: 10.1002/ecy.1578
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of two types of phenological shifts on predator–prey interactions

Abstract: Timing of phenological events varies among years with natural variation in environmental conditions and is also shifting in response to climate change. These phenological shifts likely have many effects on species interactions. Most research on the ecological consequences of phenological shifts has focused on variation in simple metrics such as phenological firsts. However, for a population, a phenological event exhibits a temporal distribution with many attributes that can vary (e.g., mean, variance, skewness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
2
19
1
Order By: Relevance
“…Alternatively, population synchrony could interact additively or synergistically with differences in species’ mean phenologies. It is difficult to intuit which case is most likely, and only one study has tested the outcomes of these concomitant shifts (Rasmussen and Rudolf ). Mean hatching time affected all five attributes of Hyla we measured in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, population synchrony could interact additively or synergistically with differences in species’ mean phenologies. It is difficult to intuit which case is most likely, and only one study has tested the outcomes of these concomitant shifts (Rasmussen and Rudolf ). Mean hatching time affected all five attributes of Hyla we measured in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to introduce tadpole hatchlings of the same size (Gosner stage 25;~2.1 mm snout-to-vent length (SVL) for Hyla and~4.4 mm SVL for Rana) on different days. These temperatures are well within the range both species would experience in ephemeral ponds in nature, and developmental assays have shown few negative side effects on performance for tadpoles reared at these temperatures (Moore 1939, Rudolf and Singh 2013, Rasmussen and Rudolf 2016. The experiment was a full 3 (phenological synchrony) 9 3 (phenological mean) factorial design.…”
Section: Experimental System and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative shifts in the phenology of species play a key role in the outcome of interspecific interactions. For instance, phenological shifts can alter predation (Alford, ; Morin, ; Rasmussen & Rudolf, ; Rasmussen et al., ), herbivory (Liu, Reich, Li, & Sun, ), pollination (Rafferty & Ives, ) and interspecific competition (Godoy & Levine, ; Hernandez & Chalcraft, ; Rudolf & Singh, ; Wilbur & Alford, ). Consistent with these studies, I found that shifting the relative timing of hatching (phenology) of a species fundamentally altered interspecific competition, but the effect of shifting the timing on competition was highly nonlinear.…”
Section: Discussionmentioning
confidence: 99%
“…Prey species can also experience notable effects on their own population dynamics when phenological shifts occur (Yang and Rudolf , Rasmussen and Rudolf ). For example, emergence synchrony can benefit prey populations by increasing the probability of finding a mate and through predator satiation, whereby the proportion of adults eaten by predators is inversely related to the number of adults present on any given day (Sweeney and Vannote , Santos et al.…”
Section: Discussionmentioning
confidence: 99%